DOI: 10.11606/d.55.2018.tde-08022018-084022
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations to the Heuristic Evaluation (HE) method for novice evaluators

Abstract: The combination of good observational skills and good design principles is a powerful tool, one that everyone can use, even people who are not professional designers. Why? Because we are all designers in the sense that all of us deliberately design our lives... " Norman (2013, p. xi-xii)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…HE is an evaluation method that focuses on evaluating an actual system or a prototype system carried out by experts. Although many previous studies have suggested that HE should be carried out by experts and not by actual users, in several studies, the evaluators were not only usability experts [31]. A detailed systematic analysis of related literature was conducted in [32].…”
Section: Introductionmentioning
confidence: 99%
“…HE is an evaluation method that focuses on evaluating an actual system or a prototype system carried out by experts. Although many previous studies have suggested that HE should be carried out by experts and not by actual users, in several studies, the evaluators were not only usability experts [31]. A detailed systematic analysis of related literature was conducted in [32].…”
Section: Introductionmentioning
confidence: 99%